Good practice in archaeological diagnostics : non-invasive survey of complex archaeological dites - Slapšak, Božidar; Vermeulen, Frank (Natural Science in Archaeology, 2013)
This volume represents the most important "deliverable" of the European-funded project Radio-Past (www.radiopast.eu). It is intended to disseminate the key results achieved in the form of methodological guidelines for the application of non-destructive approaches in order to understand, visualize and manage complex archaeological sites, in particular large multi-period settlements whose remains are still mostly buried. The authors were selected from among the project research "staff" but also from among leading international specialists who served as speakers at the two international events organized in the framework of the project (the Valle Giulia Colloquium of Rome - 2009 and the Colloquium of Ghent - 2013) and at the three Specialization Fora, the high formation training activities organized in 2010, 2011 and 2012. As such, the book offers contributions on diverse aspects of the research process (data capture, data management, data elaboration, data visualization and site management), presenting the state of the art and drafting guidelines for good practice in each field.